2017
DOI: 10.1016/j.jpain.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

“I'm Not Gonna Pull the Rug out From Under You”: Patient-Provider Communication About Opioid Tapering

Abstract: In response to increases in harms associated with prescription opioids, opioid prescribing has come under greater scrutiny, leading many health care organizations and providers to consider or mandate opioid dose reductions (tapering) for patients with chronic pain. Communicating about tapering can be difficult, particularly for patients receiving long-term opioids who perceive benefits and are using their medications as prescribed. Because of the importance of effective patient–provider communication for pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 28 publications
4
102
0
Order By: Relevance
“…Many of the challenges we identified mirror those described by clinicians caring for patients with chronic pain and opioid prescriptions generally, 8,11 as well as initiating opioid tapers specifically. 13 We identified verbal heuristics as one strategy clinicians utilize to ease conversations about opioid prescribing. Verbal heuristics were used by clinicians to routinize and increase the efficiency of the discussion, redirect responsibility away from the clinician, and defuse the potential emotional charge of the encounter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the challenges we identified mirror those described by clinicians caring for patients with chronic pain and opioid prescriptions generally, 8,11 as well as initiating opioid tapers specifically. 13 We identified verbal heuristics as one strategy clinicians utilize to ease conversations about opioid prescribing. Verbal heuristics were used by clinicians to routinize and increase the efficiency of the discussion, redirect responsibility away from the clinician, and defuse the potential emotional charge of the encounter.…”
Section: Discussionmentioning
confidence: 99%
“…For example, communication may be enhanced when patients are offered individualized reasons for tapering, clinicians express empathy through the process, and opioid tapers are designed with patient input. 13 Safety messages have also been shown to be better received by patients prescribed LTOT than rule-following messages. 23 Finally, it has been recommended that clinicians strive to replace a law enforcement or deal-making approach to opioid prescribing focused on patient behavior-where clinicians aim to Bcatch^patients or negotiate with them-with a framework that weighs benefits to harms of the medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter point is especially important given that studies of patients' tapering experiences have found that, while patients generally understand the global risks of opioids, they tend not to believe that such risks apply to them. 5,6 Consequently, tapering these patients could result in dissatisfaction with care, ultimately leading to care termination. To mitigate this risk and enhance patient understanding of opioid tapering, strategies in which providers tailor their messages to a patient's particular health concerns and how opioids may exacerbate these health concerns (e.g., explaining to a patient with pulmonary disease that opioids may depress respiratory function) may be an important tool to gain patient buy-in to opioid tapering, which presumably could reduce the risk of termination of care.…”
mentioning
confidence: 99%
“…To mitigate this risk and enhance patient understanding of opioid tapering, strategies in which providers tailor their messages to a patient's particular health concerns and how opioids may exacerbate these health concerns (e.g., explaining to a patient with pulmonary disease that opioids may depress respiratory function) may be an important tool to gain patient buy-in to opioid tapering, which presumably could reduce the risk of termination of care. 5 Another important consideration prior to and during tapering is patient input into the process. Patient involvement in treatment decisions has been shown to be associated with higher patient satisfaction, better treatment adherence, and, in some cases, better patient outcomes.…”
mentioning
confidence: 99%